Enhancing water use efficiency and fruit quality in jujube cultivation: A review of advanced irrigation techniques and precision management strategies - Yingying Xing; Mengru Chen; Xiukang Wang (Agricultural Water Management)
Jujube trees play a crucial role in sustainable agriculture in China's water-scarce regions due to their exceptional drought resistance and adaptability to arid environments. However, there is an urgent need to enhance water use efficiency and improve fruit quality in jujube cultivation to meet the growing agricultural demands. This literature review explores current strategies for water utilization in jujube tree cultivation, focusing on advanced irrigation techniques and their effects on fruit yield and quality. The review systematically examines precise irrigation management practices tailored to the critical growth stages of jujube trees. Key findings indicate that the adoption of precise irrigation strategies, such as drip and micro-irrigation, minimizes water waste and effectively meets the specific water requirements of jujube trees. Innovative contributions highlighted in the review include the integration of advanced intelligent irrigation systems that utilize soil moisture monitoring, weather data analysis, and combined water-fertilizer management. These technologies enhance the automation and precision of irrigation practices, thereby reducing reliance on external water sources, improving soil moisture retention, decreasing erosion, and mitigating environmental pollution. The review underscores the importance of novel practices such as biopolymer-based fertilizers, the intelligent integration of water and fertilizers, and IoT-based frameworks, all of which significantly enhance water use efficiency and economic productivity in jujube cultivation. The integration of full ground mulching, strategic fertilization, advanced irrigation systems, and predictive modeling constitutes a critical approach to effective water resource management. In conclusion, optimizing water resource management through precise irrigation techniques and intelligent monitoring is essential for enhancing jujube yield, fruit quality, and economic benefits. The findings highlight the necessity of adopting advanced technologies and management practices that are specifically tailored to the physiological needs of jujube trees and the unique regional conditions. Future research should focus on developing more sophisticated irrigation technologies and intelligent management systems to promote sustainable practices, alleviate water scarcity, and minimize the environmental impact of jujube cultivation.